1997
DOI: 10.1177/014572179702300505
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Diabetes Nutrition Education Increases Knowledge and Self-Efficacy of Medical Students

Abstract: Medical students and physicians need to improve their understanding of the role of nutrition and the multidisciplinary team in diabetes care. To assist in this learning, an interactive computer program was developed that focused on prescribing diets for patients with diabetes. Parallel 10-item knowledge tests and an 8-item self-efficacy scale were used to evaluate the efficacy of the computer program among 41 third-year medical students. Mean knowledge scores increased significantly after using the computer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…However, when students were given the same set of questions 6 months later, scores declined, and were no better than the control group. Several previous studies assessing short-term educational interventions and exclusively evaluating short-term outcomes have reported similar findings [15, 21, 27, 28]. This may represent effective presentations and/or the advantages of short-term memory.…”
Section: Discussionsupporting
confidence: 59%
“…However, when students were given the same set of questions 6 months later, scores declined, and were no better than the control group. Several previous studies assessing short-term educational interventions and exclusively evaluating short-term outcomes have reported similar findings [15, 21, 27, 28]. This may represent effective presentations and/or the advantages of short-term memory.…”
Section: Discussionsupporting
confidence: 59%
“…For example, Kipp (1997) reported a positive response by ®rst year medical students to computerized modules accessible on the world wide web. Engel et al (1997) found the web an effective method for delivering diabetes nutrition education to third year medical students (http:aamedicine.aecom.yu. eduadiabetesaDE.htm).…”
Section: S92mentioning
confidence: 99%
“…19 Self-effi cacy has been successfully used in educational programs for diabetes patients. [20][21][22][23] The lack of instruments adapted and validated for the Brazilian population has been a barrier for conducting studies relating to this population. We found in the literature many instruments that evaluate self-effi cacy in diabetes cases: the Diabetes Empowerment Scale (DES) and the Diabetes Self-Effi cacy Scale (DSES), which evaluate self-effi cacy in type 1 and 2 diabetics; 24,25 the Self-Effi cacy in Adolescent Girls and Boys With InsulinDependent Diabetes Mellitus scale, which is specifi c for type 1 diabetics; 16 and the Insulin Management Diabetes Self-Effi cacy Scale (IMDSES).…”
Section: Introductionmentioning
confidence: 99%